The settlement patterns of Britain - Green, Nick, 1965- author.
1 online resource (viii, 192 pages)
Keywords: "In writing The Settlement Patterns of Britain Nick Green was inspired by the short story genre. His book is a collection of eight non-fiction short stories or essays, where the characters are the places, some of which appear more than once, usually as bit-part players, occasionally as the main protagonist. Preceded by a prologue describing Britain's prehistory as a European peninsula, each essay covers a fixed period in the history of the development of Britain's settlement patterns, sometimes long, more often quite short, beginning around 2,500 BC and ending about one hundred years in the future. Nick Green chose those periods that are particularly instructive in revealing how settlement patterns come to exist in the form they do and how they might develop in the future. Settlement patterns are not just about where a place is, but about how that place relates to others. They wax and wane with circumstance, and around each settlement's fixed core, the patterns of living and working shift constantly, driven by forces beyond the control of any individual town or city or village. From Bronze Age communities to computer simulations, from the mediaeval wool trade to the hyper-networked society, from Viking invasions to the post-industrial era, the essays cover a broad sweep of history. They appear in chronological order, but are not intended to provide a continuous, linear historical narrative - nor do they: each essay is freestanding so they can be read in whatever order the reader prefers"--